Genome-Wide Study of Hsp90 Gene Family in Cabbage (Brassica oleracea var. capitata L.) and Their Imperative Roles in Response to Cold Stress - Sajad, Shoukat; Jiang, Shuhan; Anwar, Muhammad; Dai, Qian; Luo, Yuxia; Hassan, Muhammad A.; Tetteh, Charles; Song, Jianghua (Frontiers in Plant Science, 2022)
Heat shock protein 90 (Hsp90) plays important role in plant developmental regulation and defensive reactions. Several plant species have been examined for the Hsp90 family gene. However, the Hsp90 gene family in cabbage has not been well investigated to date. In this study, we have been discovered 12 BoHsp90 genes in cabbage (Brassica oleracea L var capitata). These Brassica oleracea Hsp90 genes were classified into five groups based on phylogenetic analysis. Among the five groups, group one contains five Hsp90 genes, including BoHsp90-1, BoHsp90-2, BoHsp90-6, BoHsp90-10 and BoHsp90-12. Group two contain of three Hsp90 genes, including BoHsp90-3, BoHsp90-4 and BoHsp90. Group three only includes one BoHSP90 gene, including BoHsp90-9. Group four were consisting of three Hsp90 genes including Bohsp90-5, Bohsp90-7 and BoHsp90-8, and there is no Hsp90 gene from B. oleracea in the fifth group. Synteny analysis showed that a total of 12 BoHsp90 genes have a collinearity relationship with 5 Arabidopsis genes and 10 Brassica rapa genes. The promoter evaluation revealed that the promoters of Brassica oleracea Hsp90 genes included environmental stress-related and hormone responsive cis-elements. The online tissue-specific expression analysis of BoHsp90 genes revealed that two BoHsp90-9 and BoHsp90-5 were highly expressed in stem, leaves, silique, and flowers. Furthermore, the expression pattern of Brassica oleracea BoHsp90 exhibited that BoHsp90-2, BoHsp90-3, BoHsp90-7, BoHsp90-9, BoHsp90-10, and BoHsp90-11 were induced under cold stress, which indicates these Hsp90 genes perform a vital role in cold acclimation and supports in the continual of normal growth and development process. The cabbage Hsp90 gene family was found to be differentially expressed in response to cold stress, suggesting that these genes play an important role in cabbage growth and development under cold conditions.